TM6SF2 Glu167Lys polymorphism is associated with low levels of LDL‐cholesterol and increased liver injury in obese children. Issue 2 (20th April 2015) - Grandone, A.; Cozzolino, D.; Marzuillo, P.; Cirillo, G.; Di Sessa, A.; Ruggiero, L.; Di Palma, M. R.; Perrone, L.; Miraglia del Giudice, E.
Summary: Background: The Glu167Lys (E167K) transmembrane 6 superfamily member 2 ( TM6SF2 ) variant has been associated with liver steatosis, high alanine transaminase (ALT) levels and reduced plasma levels of liver‐derived triglyceride‐rich lipoproteins. Objectives: The objectives of this study were to investigate in a group of obese children the association among the 167K allele of TM6SF2 gene and ALT, cholesterol and triglycerides levels, and hepatic steatosis, and to evaluate the potential interaction between this variant and the I148M patatin like phospholipase 3 gene ( PNPLA3 ) polymorphism on liver enzymes. Methods: We genotyped 1010 obese children for TM6SF2 E167K and PNPLA3 I148M polymorphisms. Anthropometrical and biochemical data were collected. Ultrasound imaging of the liver was performed. Results: The 167K allele showed an association with steatosis ( P < 0.0001), higher ALT levels ( P < 0.001) and lower total cholesterol ( P < 0.00001), low‐density lipoprotein cholesterol ( P < 0.0001), triglycerides ( P = 0.02) and non‐high‐density lipoprotein cholesterol levels ( P < 0.000001). The subjects homozygous for the PNPLA3 148M allele carrying the rare variant of TM6SF2 showed an odds ratio of 12.2 (confidence interval 3.8–39.6, P = 0.000001) to present hypertransaminasaemia compared with the remaining patients. Conclusion: Although the TMS6SF2 E167K variant predisposes the obese children to non‐alcoholic fatty liver disease, there is an association between this variant and lower levels of cardiovascular risk factors. Overall, the data suggest differential effects of TMS6SF2 E167K variant on liver and heart health.